Risk factors affecting the utilization of eye care services evaluated by the CDC's behavior risk factor surveillance system from 2018 to 2021 - Powers, Adrianna M.; Patel, Deepkumar; DeAngelis, Margaret M.; Feng, Changyong; Allison, Karen (Frontiers in Public Health, 2024)
When thinking about major health concerns in the U.S. and around the world, eye care is at the botom of the list compared to cardiovascular disease, cancer, and diabetes. However, people do not think about the direct connection between diabetes and eye health. Untreated diabetes can lead to visual impairment such as blindness or difficulty seeing. Studies have found eye health is associated with nutrition, occupational exposure, diabetes, high blood pressure and heart disease are some of the known risk factors. Our aim was to identify the potential risk factors that are associated with being VI. The data used for this analysis were obtained from the Center of Disease Control and Prevention (CDC) behavioral risk factor surveillance system (BRFSS) between the years 2018 and 2021. We found important characteristics such as U.S. region, general health perception, employment status, income status, age and health insurance source that are associated with VI. Our study confirmed that the common demographical factors (age, race/ethnicity, U.S. region, gender) are associated with VI. The study also adds an association with the following risk factors, health insurance source, general health perceptions, employment status and income status. With this information, we can reach out to communities with large numbers of individuals experiencing vision challenges and help educate them on prevention and treatment protocols, thereby effectively addressing VI and blindness challenges within our communities, neighborhoods, and ultimately, the broader society.